Research on the Mechanism of Urban Population in the Process of Urban Housing Price Differentiation - Chengming Yu; Shubin Miao (SAGE Open)
In recent years, the dynamics of housing prices have garnered significant attention in China, particularly the inter-city relationships of these prices. Despite its relevance, scholarly discourse has been somewhat constrained by the limitations of methodologies and the depth of discussion, leaving the underlying mechanisms inadequately elucidated. Anchored in the theoretical framework of new economic geography, this study embarks on a comprehensive examination of urban population, integrating pertinent macroeconomic variables to refine the theoretical model concerning the inter-urban housing price dynamics from the vantage point of urban population. Methodologically, the investigation employs benchmark regression analyses and incorporates various interaction terms to assess the impact of urban population on housing price disparities and to elucidate the transmission mechanisms through which macroeconomic indicators, such as household financial behaviors, influence housing price variations via household income. Findings suggest that population plays a pivotal role in driving the disparities in housing prices across cities. Specifically, variables such as the growth rate of deposits, the growth rate of leverage ratios, and the national average growth rate of urbanization exert a positive influence on housing price differentials by impacting urban population. It meas some macro indicators related to household financial behavior can provide a theoretical explanation for urban housing price differentiation. This study contributes to the existing literature by bridging identified gaps, unraveling the mechanisms through which population influences purchasing behaviors, and the allocation of household assets and liabilities. Moreover, it offers critical insights for governmental bodies in crafting policies aimed at stabilizing the investment cycle with precision, which also provides reference suggestions for household investment and savings behavior.